Using Evidence and Data to Design an Intervention in the Project Community Model for Fostering Health and Wellbeing Among Adolescent Mothers and Their Children - Dzabala, Nettie; Kachingwe, Mtisunge; Chikowe, Ibrahim; Chidandale, Carol; van der Haar, Lotte (Frontiers in Public Health, 2021)
This paper shows how quantitative and qualitative measurements of maternal psychosocial wellbeing in three districts in Malawi, informed decision making for an intervention that aimed at increasing wellbeing of adolescent mothers and healthy upbringing of their children. The one year design stage of the study relied on several sources of information: literature search, prior project implementation of similar projects, discussions with officials at the social welfare department and observation visits in the targeted districts informed the design of the project and the baseline study. The approaches of collecting data mentioned above were triangulated to generate baseline statistics, gaps and methods for the development of a baseline survey that generated systematically collected data of the experiences and recalls as well as the missing data from the preliminary evaluation of the existing data. The measurements and baseline data enabled the YWCA of Malawi to develop a program intervention that was holistic and tailored to the needs of the community, therefore making a greater impact on the lives of the beneficiaries. Furthermore, this paper discusses the lessons we learnt as to whether the assumptions we had were correct, and if not, what measures we took to correct the design or implementation of the project. The data also gave benchmarks for the project monitoring and evaluation.